Assisted reproductive technology and risk of asthma and allergy in the offspring: protocol for a systematic review and meta-analysis. Issue 4 (22nd April 2016) - Nwaru, Bright I; McCleary, Nicola; Erkkola, Maijaliisa; Kaila, Minna; Virtanen, Suvi M; Sheikh, Aziz
Abstract : Introduction: The use of assisted reproductive technology (ART) procedures has increased globally over the last three decades. Recent observational studies suggest that children conceived through ART may be at increased risk of asthma and atopic disease compared with children conceived naturally, but findings are mixed. We aim to synthesise the evidence on the impact of ART on the risk of asthma and atopic disease in the offspring. Methods and analysis: We will identify relevant studies by searching MEDLINE, EMBASE, Cochrane Library, ISI Web of Science, CINAHL, Scopus, Google Scholar, AMED, Global Health, PsychINFO, CAB International and the WHO Global Health Library from 1978 to 2016. We will locate additional studies through searching databases of the proceedings of international conferences, contacting international experts in the field, and searching the references cited in identified studies. We will include analytic observational studies (cohort studies, case–control studies and cross-sectional studies) that have investigated the impact of any type of ART on offspring's asthma and atopic disease. Screening of identified records, data extraction from eligible studies and risk of bias assessment of eligible studies will be independently undertaken by two reviewers, with arbitration by a third reviewer. The Effective Public Health Practice Project will be employed for risk of bias assessment. Estimates from studies judged to be clinically, methodologically and statistically homogeneous will be synthesised using random-effects meta-analysis. Ethics and dissemination: As this study is based solely on the published literature, no ethics approval is required. We will publish our findings in a peer-reviewed scientific journal and present the results at national and international scientific conferences. Protocol registration: We will register a detailed protocol for the review with the International Prospective Register of Systematic Reviews (PROSPERO) prior to starting the review.